Aries Ville Enterprise - Masrani, Aisyah Najihah; Muslimin, Farazilamasni; Jaafar, Jafita; A. Mojitoh, Marsha Babie; A. Karin, Nadia (2012)
We are graduates of UiTM Kota Kinabalu Sabah of Diploma in Business Studies. We chose to form a business partnership in agriculture field. Aries Ville Enterprise made up of five members; AisyahNajihahMasrani, JafitaJaafar, Nadia A.Karim, FarazilamasniMuslimin and Marsha BabieMojitoh. Our company breeds Boer goat. The main activities of our business are breeding goats and supply livestocks for "Akikah" and for "Qurban" (slaughtering). Our business will be operating at KampungTimbangDayang, Kota Belud.